Structural investigation of cell wall polysaccharides of Lactobacillus delbrueckii subsp. bulgaricus 17. (2nd September 2015) - Vinogradov, E.; Sadovskaya, I.; Cornelissen, A.; van Sinderen, D.
Abstract: Lactobacilli are valuable strains for commercial (functional) food fermentations. Their cell surface-associated polysaccharides (sPSs) possess important functional properties, such as acting as receptors for bacteriophages (bacterial viruses), influencing autolytic characteristics and providing protection against antimicrobial peptides. The current report provides an elaborate molecular description of several surface carbohydrates of Lactobacillus delbrueckii subsp. bulgaricus strain 17. The cell surface of this strain was shown to contain short chain poly(glycerophosphate) teichoic acids and at least two different sPSs, designated here as sPS1 and sPS2, whose chemical structures were examined by 2D nuclear magnetic resonance spectroscopy and methylation analysis. Neutral branchedsPS1, extracted with n -butanol, was shown to be composed of hexasaccharide repeating units (-[α-d -Glc p -(1-3)-]-4-β-l -Rha p 2OAc-4-β-d -Glc p -[α-d -Gal p -(1-3)]-4-α-Rha p -3-α-d -Gal p -), while the major component of the TCA-extractedsPS2 was demonstrated to be a lineard -galactan with the repeating unit structure being (-[Gro-3 P -(1-6)-]-3-β-Gal f -3-α-Gal p -2-β-Gal f -6-β-Gal f -3-β-Gal p -). Graphical abstract: Highlights: First description of the surface-associated carbohydrates of a Lactobacillus delbrueckii strain. Short chain poly(glycerophosphate) teichoic acids, but no lipoteichoic acids detected. Unique linear glycerol-3-phosphorylatedd -galactan. Hydrophobic polysaccharide with an Rha2OAc residue in the hexasaccharide repeat.